Tardy posterior interosseous nerve palsy associated with operated proximal shaft of radius fracture: a rare case report - Bansal, Amit (International Journal of Research in Orthopaedics, 2020)
Tardy Posterior interosseous nerve palsy (PIN) is rare diagnosis. It is a mostly motor nerve. It is prone to injury around radio-humeral joint due to its proximity to joint and neck of radius. Early diagnosis is must to improve recovery. In our case, 39-year-old male presented with tardy PIN palsy secondary to united proximal shaft radius fracture with implant in situ. Electrodiagnostic studies revealed motor radial neuropathy left upper limb. Magnetic resonance imaging (MRI) brachial plexus and screening of cervical spine was normal. After preoperative investigation, patient underwent PIN neurolysis with plate removal. Postoperatively patient started showing improvement after 2 months. Patient recovered to achieve good grip at end of 8 months. Early diagnosis followed by nerve exploration is necessary for good recovery and improvement.